The lexical-thematic paradigm of the colour black in the idiostyle of E. M. Remarque - Капніна, Галина Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The purpose of the research is to structure collocations with the «schwarz» element by lexical-thematic groups and their characteristics, which made possible the identification of all semantic variations of the colour black in the idiostyle of E. M. Remarque and helped to reveal the shades of their meaning in the process of reader’s perception of this prominent writer’s works. To achieve its stated goals the study involved the integrational use of general scientific methods (description, induction, deduction), as well as the analysіs of dictionary definitions, modelling and classification of the actual material. The lexical-thematic paradigm of the colour black in the idiostyle of E. M. Remarque is represented by collocations to describe character appearance, shoes and clothes; the plant and animal world, the environment, natural phenomena; household items, building structures, transport; lighting, shapes and figures; forbidden actions and malpractice; people’s mental and physical states. The first group was found to be the most numerous one, while the group which describes people’s severe mental or physical conditions comprised the smallest number of collocations, which make up the black palette of E. M. Remarque’s works. Analysed coloronym (every fourth adjective to denote the colour) is the most actively used by the author in his work „Liebe deinen Nächsten“. The detailed analysis of the writer’s discourse shows that the colour dominant „schwarz” is an important element of the author’s creative method. It is not used to remove colour from reality; it paints it in dark colours, contributes to the formation of the emotional component of the text and stimulates the associative activity of the reader.